Grassland ecological compensation policy in China improves grassland quality and increases herders’ income - Lingling Hou (Nature Portfolio, 2021)
China has introduced a payment-for-ecosytsem-services program called GECP which is focused on pastoral communities in grassland areas. Here, the authors combine remote sensing and household survey data to find small improvement in grassland quality and a significant positive effects on the income of herders.